2014
DOI: 10.1111/tri.12370
|View full text |Cite
|
Sign up to set email alerts
|

New nucleos(t)ide analogue monoprophylaxis after cessation of hepatitis B immunoglobulin is effective against hepatitis B recurrence

Abstract: SummaryNew nucleos(t)ide agents (NAs) [entecavir (ETV) and tenofovir (TDF)] have made hepatitis B immunoglobulin (HBIG)-sparing protocols an attractive approach against hepatitis B virus (HBV) recurrence after liver transplantation (LT). Twenty-eight patients transplanted for HBV cirrhosis in our centre were prospectively evaluated. After LT, each patient received HBIG (1000 IU IM/day for 7 days and then monthly for 6 months) plus ETV or TDF and then continued with ETV or TDF monoprophylaxis. All patients had … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
40
2
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(46 citation statements)
references
References 21 publications
3
40
2
1
Order By: Relevance
“…Subsequently, HBIG was discontinued and patients were followed for a median 21 months. Both HBsAg and HBV DNA remained negative in all patients [24].…”
Section: Hbig For a Certain Periodmentioning
confidence: 94%
“…Subsequently, HBIG was discontinued and patients were followed for a median 21 months. Both HBsAg and HBV DNA remained negative in all patients [24].…”
Section: Hbig For a Certain Periodmentioning
confidence: 94%
“…Subsequently, HBIg was discontinued and patients were followed for a median 21 months. Both HBsAg and HBV DNA remained negative in all patients [14]. In a different study, 80 patients were followed for 26-month post-transplant using entecavir monotherapy that was initiated prior to transplant.…”
Section: Renal Function Esrd On Hd Normalmentioning
confidence: 98%
“…Cholongitas et al [14] reported the efficacy of entecavir or tenofovir as monotherapy in preventing HBV recurrence in CHB patients who underwent OLT previously treated with HBIg. Eleven patients with entecavir and 17 patients with tenofovir received HBIg for 6 months.…”
Section: Renal Function Esrd On Hd Normalmentioning
confidence: 98%
See 1 more Smart Citation
“…Cholongitas et al studied patients who were transplanted for HBV cirrhosis and were treated with a 6-month HBIG protocol combined with either ETV or TDF as prophylaxis [20]. A total of 28 patients were enrolled into the study, with 17 of the patients treated with ETV and the other 11 with TDF.…”
Section: Hbig Withdrawal After 6 Monthsmentioning
confidence: 99%